QTIPs: Questionable theoretical and interpretive practices in social psychology. (8th September 2015) - Brandt, Mark J.; Proulx, Travis
Abstract: One possible consequence of ideological homogeneity is the misinterpretation of data collected with otherwise solid methods. To help identify these issues outside of politically relevant research, we name and give broad descriptions to three questionable interpretive practices described by Duarte et al. and introduce three additional questionable theoretical practices that also reduce the theoretical power and paradigmatic scope of psychology.